POTENTIALS OF POULTRY INSURANCE SCHEME AS A RISK MANAGEMENT TECHNIQUE FOR NIGERIAN FARMERS - ADESIMI , A. A.; AWOYOMI, B. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
This paper is an attempt to illustrate how the establishment and operation of a poultry insurance scheme in Nigeria can aid in minimizing the incidence of income loss due to high mortality rates in poultry farming. Attention is drawn to the paucity of mortality data as a major bottleneck in instituting the scheme. The study utilizes empirical data from the Nigerian experience to show the outlines and logistics of a suggested scheme (type of data, terms. contracts, premium and indemnity calculations).